Hak-hak Konstitusional Anak terkait Penelantaran Akibat Perceraian - Yusnani Hasyimzum (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2021)
Children, both boys and girls, are considered state assets because they represent the nation's future generation. Children's development and growth require special consideration and protection on the part of parents, family, society, nation, and state. Children's constitutional rights are regulated in the 1945 Constitution, which guarantees the welfare of every citizen, including protection against violations of children's rights, which are considered human rights. Every child has the right to survival, growth, and development, as well as the right to be protected from violence and discrimination, as mandated by the 1945 Constitution of the Republic of Indonesia; additionally, every child has the right to survival, growth, and development, as well as the right to be protected from violence and discrimination; The issue is why the constitutional rights of children who have been neglected as a result of divorce have not been fully complied with and what legal safeguards have the government implemented to reduce the number of child neglect victims.